ANALISIS PEMBENTUKAN PORTOFOLIO OPTIMAL MENGGUNAKAN MODEL INDEKS TUNGGAL UNTUK PENGAMBILAN KEPUTUSAN INVESTASI (Studi Pada Saham Lq-45 Di Bursa Efek Indonesia Periode 2009-2013) - B11110137, DODI MAULANA (Jurnal Manajemen Update, 2015)
This study directed to analyze the formation of optimal portfolio shares in the Indonesian Stock Exchange during the period from 2009 to 2013. The sample in this study using an active stock by frequency trade transactions and respectively dividend payment by the company during the period 2009-2013 by using single index model method. The purpose of this study was to know the shares of LQ 45 which can be used as forming an optimal portfolio and how much the proportion of funds, determine the magnitude of expected return and risk of the portfolio that is formed and to know the difference between incoming return portfolio candidateswith that who do not make the candidate portfolios. This research is descriptive with quantitative approach. The data used is secondary data analysis of the data using Single Index Model application. Results of the analysis in this study has selected 10 shares of LQ 45 which is forming an optimal portfolio and the proportion is as follows INDF at 6.59%, KLBF amounted to 7.09%, BII amounted to 7,77%, INTP amounted to 9.63% , ADRO by 10.05%, amounting to 10.26% JSMR, ASII of 10.50%, amounting to 10.87% ITMG, BMRI amounted to 12.13%, and amounted to 15.11% SMGR. Single Index optimal portfolio based on this model provides a portfolio of 0.582708 expectations or 58.27%., While for the risk of the portfolio is formed by 0.324522, or 32.45%. From the test results raised the hypothesis that it can be concluded that appear between stock returns candidates who entered the portfolio with stock returns that do not make the candidate portfolio paddock there is a difference significant value of 5% (0,231>0,50),then the investor should choose stocks included in candidate portfolio. Investors should be using Single Index Model because it can obtain the expected return with the lowest return and investors who invest in stocks should perform on several stock diversification to reduce risk. Keywords: optimal portfolio, risk, and return